I’dad Al-Kitabi At-Ta’limiy Li Maaddati Al-Khatti Al-Arabiy Bi Ma’had Al-Mukhlishin Batu Bara Sumatera Asy-Syamaliyah - Ainul Mardiah (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2021)
The aim of this research is to know the preparation of the textbook for Arabic calligraphy, to describe the validity of the textbook for Arabic calligraphy, and to know the effectiveness of the textbook for Arabic calligraphy among students at the Al-Mukhlisin Islamic Boarding School Batu Bara, North Sumatra. The problem in learning calligraphy for female students of the Al-Mukhlisin Islamic Boarding School in Batu Bara, North Sumatra is the students' weak ability in calligraphy, this is because there are no textbooks as the main reference for them and the calligraphy teacher. The teacher provides material from various sources that are not used as a book or module without seeing the goals and targets to be achieved in calligraphy learning. Due to time constraints students have difficulty repeating letter exercises in the dormitory because there are no manuals to re-study so learning like this is less effective according to the researcher. Responding to this, the researcher tried to provide a solution by making the calligraphy textbook Khat Naskhi to make it easier for teachers and students to reach calligraphy book references. Khat naskhi is a basic Khat that is easy to imitate and read which is widely applied in Indonesia. The research method is a type of R&D with the Borg & Gall model, the research instrument is carried out by observation, interviews, questionnaires, tests and documentation. Researchers conducted product feasibility tests with experts / experts in the field of calligraphy, and researchers conducted product trials on female dormitory students at the Al-Mukhlisin Islamic Boarding School to determine the effectiveness of books using the pre-test and post-test systems. The results of this study are: 1) the realization of a textbook product for calligraphy material. 2) After going through the feasibility validation test, this product was declared feasible with a value of 89%. 3) the results of the product effectiveness test to students, the researcher obtained a t-count value of 7.863 which is greater than t-table 2,000 with an error percentage of 5%, then the hypothesis is accepted and the product developed is declared effectiv